2023
DOI: 10.3389/fpubh.2022.1047965
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing to characterize the genetic structure and transmission risk of Mycobacterium tuberculosis in Yichang city of China

Abstract: ObjectiveThe burden of both general and drug-resistant tuberculosis in rural areas is higher than that in urban areas in China. To characterize the genetic structure and transmission risk of Mycobacterium tuberculosis in rural China, we used whole genome sequencing to analyze clinical strains collected from patients in two counties of Yichang for three consecutive years.MethodsFrom 2018 to 2020, sputum samples were collected for cultures from patients with suspected tuberculosis in Yidu and Zigui county, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
5
2
Order By: Relevance
“…The results showed that more than 10% of the strains belong to MDR/RR-TB, which is higher than the national level in China (7.42%), 7 but similar to the level of Yichang city (11.3%). 27 In addition, low fluoroquinolone resistance rate was detected in this study, which is inconsistent with reports from other provinces in China. 17 , 22 , 27 The conflicting result might be due to the frequency and dosage of fluoroquinolone antibiotics used in different regions or the strains selected for the research.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The results showed that more than 10% of the strains belong to MDR/RR-TB, which is higher than the national level in China (7.42%), 7 but similar to the level of Yichang city (11.3%). 27 In addition, low fluoroquinolone resistance rate was detected in this study, which is inconsistent with reports from other provinces in China. 17 , 22 , 27 The conflicting result might be due to the frequency and dosage of fluoroquinolone antibiotics used in different regions or the strains selected for the research.…”
Section: Discussioncontrasting
confidence: 99%
“… 27 In addition, low fluoroquinolone resistance rate was detected in this study, which is inconsistent with reports from other provinces in China. 17 , 22 , 27 The conflicting result might be due to the frequency and dosage of fluoroquinolone antibiotics used in different regions or the strains selected for the research. However, this finding favors future applications of fluoroquinolones in TB treatment regimens of shorter duration.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…5 [15]. In some areas over 30% of the RR-TB patients are already resistant to FQ, pre-XDR, at the start of the treatment [16]. Therefore, implementing the Xpert MTB/XDR test means that more patients will be initiated to DST guided TB treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In some settings over 30% of the RR-TB patients are already resistant to FQ, i.e. pre-XDR, at the start of the treatment [ 14 ]. Therefore, implementing the Xpert MTB/XDR test means that more patients will be initiated to DST-guided TB treatment regimen.…”
Section: Discussionmentioning
confidence: 99%